Foliar Application of Boron during Flowering Promotes Tolerance to Cocoa (Theobroma cacao L.) Swollen Shoot Viral Disease - Sara Georgina Kouadio; Eric-Olivier Tienebo; Kouakou Théodore Kouadio; Koffi Badou Jérémie Kouamé; Louis Koko; Kouabenan Abo (European Scientific Journal, ESJ, 2017)
Boron nutrition is known to reduce the effect of some viral and fungal diseases on plant fitness. This study investigated the potential of boron application to improve yield and tolerance of cacao trees naturally infected by virulent cocoa swollen shoot virus (CSSV) strains and determined the effective dose and time of application. Foliar sprays of a commercial product containing 20.5% of boron were performed either at the onset of flowering’s peak of the little milking (early in November) or four weeks later (early in December) with four doses of boron (0, 31.25, 41.67, and 83.27 g/ha) in a randomized complete block design with four replications. We found that boron application improved foliar density and induced production of pods of normal shape meanwhile reducing the appearance of this misshapenness due to CSSV. Boron also increased the number of emitted flowers, cherelles and pods subsequently. Moreover, weight and size of fresh cocoa beans per pod were positively correlated to boron dosage. Interestingly, foliar sprays performed early in November resulted in less flat cocoa beans. Finally, the optimal dose of boron that reduced the adverse effects of the most virulent form of cocoa swollen shoot viral disease is 41.67 g/ha.